Perceived Value and Product Quality Associations with Loyalty in Salted Egg SMEs : Hubungan Perceived Value dan Kualitas Produk dengan Loyalitas pada UKM Telur Asin - Purbaningtyas, Amelia; Waluyo, Minto (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Micro, Small, and Medium Enterprises (MSMEs) play a critical role in economic stability, requiring strategies to sustain customer loyalty in competitive markets. Specific Background: The salted egg SME industry faces declining sales, operational inconsistencies, and challenges in maintaining product quality and perceived value, which affect consumer behavior. Knowledge Gap: Previous studies have not comprehensively integrated product quality, customer experience, and perceived value into a sequential behavioral model linking purchase intention, satisfaction, repeat purchase, and customer loyalty. Aims: This study aims to analyze the relationships among product quality, customer experience, and perceived value on purchase intention, satisfaction, repeat purchases, and customer loyalty using Structural Equation Modeling (SEM). Results: The findings indicate that perceived value and product quality significantly and positively affect purchase intention, while customer experience shows a positive but insignificant relationship. Purchase intention significantly influences satisfaction, which subsequently drives repeat purchases, and repeat purchases significantly lead to customer loyalty. Novelty: This study proposes a hierarchical causal model that explains customer loyalty formation through sequential behavioral stages within salted egg SMEs. Implications: The results provide a strategic basis for SMEs to prioritize product quality and perceived value to strengthen sustainable customer loyalty and guide future research in developing more comprehensive behavioral models. Highlights: Value perception shows the strongest contribution in shaping early-stage consumer decisions. Sequential linkage from intention to satisfaction and repurchase forms a continuous behavioral pathway. Experiential aspects demonstrate limited statistical contribution in initial decision formation. Keywords: Perceived Value, Product Quality, Customer Experience, Customer Loyalty, Structural Equation Modeling